Enhancement in RNase H activity of a DNA/RNA hybrid duplex using artificial cationic oligopeptides. Issue 61 (16th July 2018) - Hara, Rintaro Iwata; Maeda, Yusuke; Fujimaki, Haruna; Wada, Takeshi
Abstract : This study assessed the effects of artificial cationic oligopeptides on a DNA/RNA hybrid duplex. Abstract : This study assessed the effects of artificial cationic oligopeptides on a DNA/RNA hybrid duplex. An oligopeptide containing the octamer ofl -2, 4-diaminobutyric acid (Dab8) was found to enhance both the RNase A resistance and RNase H activity of the DNA/RNA hybrid, which are important for developing nucleic acid drugs.